Study on the Numerical Model of Gas–Liquid Dispersion Driven by a Coaxial Mixer - Yang, Chao; Lu, Hancheng; Li, Zhe; Xu, Zilong; Liu, Baoqing (Industrial & engineering chemistry research, 2023)
As the flow basis for gas–liquid mixing, turbulence plays an important role in the movement of bubbles in a stirred tank. Motivated by the fact that the current models in the framework of computational fluid dynamics-population balance model lack an adequate assessment of the turbulence effects, the coaxial mixer was chosen as the subject of study, and different turbulence models, drag models, and breakup and coalescence models were compared and optimized. The results showed that the RNG k-ε model better characterized the turbulent scale and achieved a higher exactness for the gas-phase concentration in the axial direction. The Luo–Luo model modified based on the eddy capture mechanism could effectively describe the coalescence and breakup processes of bubbles. Additionally, in the presence of strong turbulence, the Ishii & Zuber model and the Brucato model outperformed other models in predicting gas dispersion and flow structure but still failed to capture the peak gas holdup. By analyzing the available data, a new correlation was proposed to elucidate the increase in drag coefficient caused by turbulence, which significantly improved the prediction accuracy of gas holdup.